Method for Evaluating the Principle of Interculturality in the Custodial Sentence using the Iadov Technique - Danilo Andrade Santamaría; Jorge Washington Soxo Andachi; Oscar Fabián Silva Montoya (Neutrosophic Sets and Systems, 2020)
The principle of interculturality represents a condition for respecting the rights of others. Assessing the state of interculturality makes it possible to especially ensure the rights of indigenous communities. However, in Ecuador the existing legal norms do not guarantee the intercultural protection of citizens in custodial sentence. This research proposes a solution to the posed problem by developing a method for evaluating the principle of interculturality in the application of a custodial sentence. The method bases its operation on using the Iadov technique. Uncertainty is modeled with the use of neutrosophic numbers. The method was applied to representative people of the indigenous communities of the Pastaza province. As a result, we obtained an assessment of the main indigenous actors in the communities on the intervention of ordinary justice in death cases.